Redefiniranje pojma izdelek za teorijo in prakso marketinga - Snoj, Boris (Akademija MM, 2012)
The overview of the relevant literature reveals the distinctive variety of explanations of concepts and terms: goods, product, commodity, service. In order to serve the marketing theory and praxis, the authors use their own approach to explain these concepts and terms. The first part of this article explores the clasification of goods, which also includes products as the objects of exchange. The second part offers a short description of basic forms of products as the objects of exchange. The notion of product from marketing viewpoint is dealt with in the central part of the article. The authors explain the mission of products, and propose their definition from the holistic marketing perspective. According to the authors, beings, things and their activities are generic product elements, realized through different basic forms of product elements. A continous consideration of target groups, internal and external environmental changes, is of vital importance for organizations if they want successful products in competitive markets. Therefore, organizations try to attain competitive advantages by increasing the complexity of their products. In the end, the authors discuss the role of organizations and target groups in (co)creating a potential and realized product value.
Keywords: izdelki; marketing; proizvodi; storitve; trženje